#### Answer

$-1\frac{23}{24}$

#### Work Step by Step

$11\frac{7}{8}-13\frac{5}{6}$
$=-13\frac{5}{6}+11\frac{7}{8}$
$=-(13\frac{5}{6}-11\frac{7}{8})$
$=-(13\frac{20}{24}-11\frac{21}{24})$
$=-(12\frac{44}{24}-11\frac{21}{24})$
$=-1\frac{23}{24}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$-1\frac{23}{24}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.